2017
DOI: 10.1371/journal.pone.0171267
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Potential of Thymoquinone and Curcumin on Fasciola gigantica

Abstract: Fasciolosis an economically important global disease of ruminants in the temperate and tropical regions, caused by Fasciola hepatica and F. gigantica, respectively, also poses a potential zoonotic threat. In India alone it causes huge losses to stakeholders. Anthelmintics including triclabendazole have been used to control this menace but the emerging resistance against the available compounds necessitates identification of novel and alternative therapeutic measures involving plant derived natural compounds fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 63 publications
6
50
0
1
Order By: Relevance
“…Mostly, the therapeutic benefits of N. sativa are due to its richness in Thymoquinone (TQ), which is a major active constituent. In studies focusing on antiparasitic effects (ISSA, 2003), it has been found that different extracts of N. sativa, as well as TQ, have a potent anthelmintic action against Fasciola gigantica (ULLAH et al, 2017) and Schistosoma mansoni (SHENAWY et al, 2008). The results from in-vitro tests on N. sativa seeds against miracidia, cercariae and adult worms have shown that they have strong effects against all stages of the parasite and an inhibitory effect on egg-laying among adult female worms.…”
Section: In Vitro Evaluation Of Nigella Sativa and Punica Granatum Efmentioning
confidence: 99%
“…Mostly, the therapeutic benefits of N. sativa are due to its richness in Thymoquinone (TQ), which is a major active constituent. In studies focusing on antiparasitic effects (ISSA, 2003), it has been found that different extracts of N. sativa, as well as TQ, have a potent anthelmintic action against Fasciola gigantica (ULLAH et al, 2017) and Schistosoma mansoni (SHENAWY et al, 2008). The results from in-vitro tests on N. sativa seeds against miracidia, cercariae and adult worms have shown that they have strong effects against all stages of the parasite and an inhibitory effect on egg-laying among adult female worms.…”
Section: In Vitro Evaluation Of Nigella Sativa and Punica Granatum Efmentioning
confidence: 99%
“…gigantica , such as cysteine proteinases like cathepsin B, cathepsin L, glutathione S transferase and tegumental antigens such as 28.5 kDa and 66 kDa proteins [ 24 30 ]. The proteinases secreted by the parasites are important for the successful establishment of host parasite interaction including invasion, destruction of host tissues, penetration of host vascular systems, migration towards their microhabitat and these proteinases could be a promising chemotherapeutic or vaccine target [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tata cara merumput termasuk waktu pengambilan rumput merupakan faktor yang dapat mereduksi kejadian fasciolosis. Berdasarkan penelilian yang dilaksanakan oleh Ullan et al (2017), selain golongan obat albendazole, pengobatan fasciolosis dapat dilakukan dengan pemberian bahan yang mengandung timokuinon dan kurkumin. Bahan aktif yang terkandung dalam Nigella sativa dan Curcuma longa tersebut dapat alternatif dalam pengobatan fasciolosis.…”
Section: Program Pengobatan Fasciolosisunclassified